Comparison of Domestic and Foreign Safety Standards for Edible Vegetable Oils（Ⅰ） ———Comparison of System, Framework, Scope and Classification - ZHAO Chen-wei; JIN Qing-zhe; WANG Xing-guo (Liang you shipin ke-ji)
This article systematically compared the differences in edible vegetable oil safety standards among China and international organizations, countries, and regions such as the Codex Alimentarius Commission, the European Union, the United States, Japan, Australia and New Zealand, Singapore, India, South Korea, and Russia from four aspects: the standard system, text structure, scope, and classification. The study found that: in terms of the standard system, various countries formulated their own vegetable oil safety standards according to their respective national conditions. In terms of the standard text structure, the vast majority of edible vegetable oils standards in different countries included regulations related to scope, physicochemical indicators, safety indicators and labeling. In terms of scope and classification, the standards of various countries basically cover common vegetable oils and have made different classifications based on processing depth or technology according to their national conditions. This research can provide references for the formulation and revision of Chinese edible vegetable oil safety standards, in order to further improve Chinese edible vegetable oil safety standards and protect consumer health.